Measuring corrosion rate and protector effectiveness of advanced multilayer metallic materials by newly developed methods - Vladimir A. Grachev; Andrey E. Rozen; Yuri P. Perelygin; Sergey Yu. Kireev; Irina S. Los'; Andrey A. Rozen (Heliyon, 2018)
The paper estimates corrosion resistance of new multilayer metallic materials with internal protector against pitting. Using an electron microscope method, the mechanism of the layers' corrosive destruction has been experimentally substantiated. The authors have suggested chemical and electrochemical methods of accelerated corrosion tests allowing for determining the corrosion destruction rate. The electrochemical method reveals the limiting stage of the process and allows calculating the mass corrosion index and substantiating the choice of protector for the specific corrosive medium. The chemical method allows for quantitative assessment of the internal protector's effectiveness and for defining the multilayer/monometallic material corrosion resistance ratio.